Inguinal Hernia in Infants and Children - Moedito Mardjikoen, Moedito Mardjikoen (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1973)
179 cases of inguinal hernia in infants and children, including 20 incarcerated cases during the eleven-year period from January 1961 through December 1971 at the Department of Surgery, Gadjah Mada University Hospital, were reported.In accordance to most of the references attention was given to the incidence of the left side in the report ( 59,8%) which paradoxially was markedly higher than the right side ( 30,7% ).Operations were performed on 160 cases and the mortality rate was percent.